Landscape integration of North Patagonian mountain lakes: a first approach using characterization of dissolved organic matter - Garcia, Patricia Elizabeth (2015)
North-western Patagonia contains a variety of glacially formed mountain lakes located at different positions from the treeline in the Andean Patagonian forest region. Water chemistry of six North Patagonian lakes located in an altitudinal gradient, above, at and below the treeline (~41°S) were analysed in this study. The relative importance of allochtonous to autochthonous carbon inputs along a marked catchment vegetation gradient encompassing altoandino vegetation and Nothofagus forests was addressed. The dissolved organic carbon (DOC) concentration varied among the study lakes, with the lakes located higher in the landscape exhibiting lower DOC concentrations (<1 mg L−1) than lakes located at or below the treeline (>2 mg L−1). Analysis of coloured and fluorescent dissolved organic matter (CDOM and FDOM, respectively) followed the DOC pattern, despite the contrasting catchments of the study lakes. The results indicated the CDOM in all the lakes had low molecular weight and low aromaticity. The excitation–emission matrices (EEMs) highlighted three distinctive fluorophores in the FDOM, including two humic-like (peak A and peak C) revealing the presence of humic terrestrial material, and a protein-like fluorophore (peak T) generally associated with autochthonous DOM. The increased intensities of the humic fluorophores in the lakes located below the treeline suggest higher allochtonous carbon inputs from their catchments. This evidence collectively suggests that mountain lakes exhibit some heterogeneity in terms of DOM, likely attributable to their position in relation to the treeline, which determines the contribution of the catchment. As remote lakes are extremely sensitive to changes in their catchments, these North Patagonian mountain lakes may accurately track the impact of climate and anthropogenic changes on the landscape.